Drosophila Prp40 localizes to the histone locus body and regulates gene transcription and development. - Prieto-Sánchez, S.; Moreno-Castro, C.; Hernández-Munain, C.; Suñé, C. (Journal of Cell Science, 2020)
In eukaryotes, a large amount of histones need to be synthesized during the S phase of the cell cycle to package newly synthesized DNA into chromatin. The transcription and 3' end processing of histone pre-mRNAs are controlled by the histone locus body (HLB), which is assembled on the shared promoter for H3 and H4 Here, we identified the Drosophila Prp40 pre-mRNA processing factor (dPrp40, annotated as CG3542) as a novel HLB component. We showed that dPrp40 is essential for Drosophila development, with functionally conserved activity in vertebrates and invertebrates. We observed that dPrp40 is fundamental in endocycling cells, highlighting a role for this factor in mediating replication efficiency in vivo The depletion of dPrp40 from fly cells inhibited the transcription, but not the 3' end processing, of histone mRNA in a H3- and H4-promoter-dependent manner. Our results establish that dPrp40 is an essential protein for Drosophila development that can localize to the HLB and might participate in histone mRNA biosynthesis.